1992
DOI: 10.1103/physrevd.45.3128
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of Feynman scaling law and cosmic-ray exotic events

Abstract: The breakdown of the Feynman scaling law, observed at the CERN SPS pp collider (&s =540 or 900 GeV), leads to decreasing inelasticity, which is not compatible with high-energy cosmic-ray data {E0 =10' -10' eV) obtained through emulsion-chamber experiments. It is pointed out that the existence of the cosmic-ray exotic events of Centauro, Chiron, etc. , possibly reconciles the discrepancy. PACS number{s): 13.85. Tp, 13.85.Hd

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…It is defined as the fraction of energy giving up by the leading hadron in a collision induced by an incident hadron on a target nucleon or nucleus. The inelasticity, K N , in a nucleon-induced interaction is related to the spectrumweighted moments evaluated at γ = 1 (where γ is the power index of primary spectrum) as Several authors have suggested that the average inelasticity-coefficient is an increasing function of the energy [1,2], whereas others proposed that it is a decreasing function [3,4,5]. The behaviour of high energy cosmic rays, which reflects the nuclear interactions in the energy region 1 ∼ 100 TeV, indicates a constant value of the mean inelasticity equal to 0.50 [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is defined as the fraction of energy giving up by the leading hadron in a collision induced by an incident hadron on a target nucleon or nucleus. The inelasticity, K N , in a nucleon-induced interaction is related to the spectrumweighted moments evaluated at γ = 1 (where γ is the power index of primary spectrum) as Several authors have suggested that the average inelasticity-coefficient is an increasing function of the energy [1,2], whereas others proposed that it is a decreasing function [3,4,5]. The behaviour of high energy cosmic rays, which reflects the nuclear interactions in the energy region 1 ∼ 100 TeV, indicates a constant value of the mean inelasticity equal to 0.50 [6].…”
Section: Introductionmentioning
confidence: 99%
“…This behavior is analogous to the dual string model [14,15] (see also the discussions in Refs. [16] and [17]). …”
Section: Leading Particle Spectramentioning
confidence: 94%
“…With K as the normalization energy of elasticity, we use the following average model of elasticity [20] to power s…”
Section: Appendix a Methods Of Characteristics For Nucleon Diffusion mentioning
confidence: 99%
“…This parameter has been exhaustively studied in several papers, but until now continues to be an open question. Several authors have suggested that the average inelasticity coefficient is an increasing function of the energy [17,18], whereas others proposed that it is a decreasing one [19][20][21]. However, high energy cosmic rays, which reflects the nuclear interaction in the energy region covering 1 to 100 TeV , are well fitted with a constant value of the mean inelasticity equal to 0.50 [22,23].…”
Section: Introductionmentioning
confidence: 99%